Spectrophotometric determination of sperm concentration and short‐term cold‐storage of sperm in Atlantic croaker Micropogonias undulatus L. broodstock. Issue 8 (21st November 2012) - Leclercq, Eric; Antoni, Luca; Bardon‐Albaret, Agnès; Anderson, Corey R; Somerset, Carly R; Saillant, Eric A
Abstract The objective of this study was to optimize the methodology for spectrophotometric determination of sperm concentration in Atlantic croaker Micropogonias undulatus L. milt and to estimate its potential for short‐term cold‐storage. The spectrophotometric determination of sperm concentration was evaluated using milt samples from six males serially diluted in Hank's balanced salt solution at 200 mOsm kg−1 (HBSS). The predictive power of regression models between sperm concentration and absorbance was determined from 200 to 500 nm and found to be highest within the visible spectrum despite a peak of milt absorbance at 288 nm. Absorbance reading at 400 nm was selected for further analysis to maximize the absorbance of the sample hence the sensitivity of the method while minimizing the impact of potential sample contamination with blood. The standard‐curve of correlation between sperm absorbance at 400 nm and concentration was validated and held an accuracy ranging between −7.40% and +4.56% across males. Total sperm motility duration and the proportion of motile spermatozoa were significantly higher in milt samples diluted 1:3 in HBSS than in the undiluted control during up to 30 h of cold‐storage.The methodologies investigated in this study can be applied to optimize sperm usage and achieve predictable artificial fertilization protocols in Atlantic croaker.